Non-lethal sampling of phalanges for heavy metal bioaccumulation in Pelophylax nigromaculatus from historical mercury mining areas in Southwestern China - Xiaodong Zhang; Zhihong Lu; Fen Chen; Bang Li; Chuandong Yang (Scientific Reports, 2024)
Abstract The Wanshan mercury mining area (WMMA) in Guizhou Province, China, has been identified as a region at high ecological risk owing to heavy metal contamination. This study employed non-lethal sampling methods, using the phalanges of Pelophylax nigromaculatus in the WMMA as analytical material. Ten heavy metal (metalloid) elements were selected for analysis, including Hg, Cr, Mn, Ni, Cu, Zn, Cd, Pb, As, and Se. These elements were measured using inductively coupled plasma mass spectrometry (ICP-MS), while Hg was determined using atomic fluorescence spectrometry (AFS). The bioaccumulation characteristics of heavy metals in P. nigromaculatus were analyzed through the bioaccumulation factor (BAF), and the extent of heavy metal pollution along with potential ecological risk was assessed using the potential ecological risk index (RI). The scaled mass index (SMI) was utilized to evaluate the body condition of P. nigromaculatus. Additionally, a combination of Spearman correlation analysis and non-negative matrix factorization (NMF) was employed to identify the sources and contributions of heavy metal elements. The results indicated that the distribution characteristics of heavy metal elements in the phalanges of P. nigromaculatus varied. Except for Pb, the concentrations of essential trace elements were significantly higher than those of non-essential elements. The bioaccumulation potential of P. nigromaculatus for heavy metal elements in the soil was found to be low, whereas the exposure risk from heavy metals in the water was high. The presence of heavy metal elements poses a significant potential ecological risk to P. nigromaculatus, with Hg, Cd, and As identified as the primary contributors to this risk. The environmental sources of heavy metals were identified as follows: Hg, Pb, Zn, and Se mainly originated from mining pollution sources; As and Cd primarily came from atmospheric pollution sources; Cr and Cu were mainly from natural activities sources; and Mn and Ni had multiple composite sources. Although heavy metal pollution negatively impacted the physical condition of P. nigromaculatus, no significant differences in SMI were observed across different regions. We believe that this is primarily attributable to the high levels of Se, which effectively mitigate the toxicity of heavy metals. The study demonstrated that using frog phalanges for heavy metal bioaccumulation analysis and SMI for physical condition assessment are simple, safe, and non-lethal methods, which can serve as useful indicators of environmental pollution and help trace the sources of environmental pollutants.